A new genus and species of Sclerodactylidae (Echinodermata: Holothuroidea: Sclerothyoninae) from the Pacific coast of Panama, and assignment of Neopentamera anexigua to Sclerothyoninae - Martins, Luciana; Tavares, Marcos (Zootaxa, 2018)
Paulayellus gustavi, a new sclerodactylid genus and species, is described from the Pacific coast of Panama. The new genus and species is assigned to the subfamily Sclerothyoninae based on a suite of characters, which include the radial and interradial plates of the calcareous ring united at the base only. Paulayellus gen. nov. differs from the other Sclerothyoninae genera in having posterior processesof radial plates undivided. Additionally, differs from Sclerothyone, Thandarum and Neopentamera in having knobbed buttons, plates and cups in the body wall (whereas the body wall is furnished only with tables and plates in Sclerothyone, Temparena and Thandarum, and only with knobbed buttons and plates in Neopentamera). The new genus is, so far, monotypic. The also monotypic genus Neopentamera proved to have the radial and the interradial plates of the calcareous ring united at the base only, as typically found in the Sclerothyoninae, and is therefore transferred to that subfamily. The discovery of a new genus in the Sclerothyoninae and the transfer of Neopentamera required the amendation of the diagnosis for the subfamily. A key to the Sclerothyoninae is given.